Testing Segregation Measurements in Milwaukee : Reality and Perception. - Kelly, Joseph (My University, 2009)
Milwaukee, Wisconsin is widely known as the most segregated city in the United States. This study, employing an index developed from each of Massey and Denton?s five categories of Hypersegregation (evenness, exposure, concentration, centralization and clustering), evaluates residential segregation in the city of Milwaukee, WI. Aimed at aiding public policy development, this study expands the Massey and Denton model by adding variables besides race, namely education, income, home ownership, distance to public transportation, and unemployment.
Color poster with text, maps, images, and graphs describing research conducted by Joseph Kelly, advised by Lisa Theo, Patricia A. Quinn, and Monty K. Ernst.
Keywords: Milwaukee (Wis.)--Social conditions; African Americans--Segregation--Wisconsin--Milwaukee; Segregation--Wisconsin--Milwaukee; Posters